HUBUNGAN JOB EMBEDDEDNESS DAN BUDAYA KOLEKTIVISME PADA KARYAWAN GENERASI X DAN Y DI PLTD SIANTAN, KALIMANTAN BARAT - Anjini Sutampi; Aditya Nanda Priyatama; Selly Astriana (Universitas Bunda Mulia, 2018)
ABSTRACT: The company currently recognizes two types of workforce generations based on age, namely generation X and generation Y. Both generations have different characteristics, one of them is job embeddedness. Job embeddedness rate was found the highest in an organization with collectivism. An organizational culture that is developed in various companies in Indonesia is the collectivism culture, one of them is in PLTD Siantan, Kalimantan Barat.This study aims to (1) find out the differences in the tendency of job embeddedness on generation X and generation Y employees in terms of collectivism culture, (2) find out the differences of job embeddedness tendency in generation X and generation Y employees; (3) find out the differences of collectivism culture on generation X employees and generation Y in PLTD Siantan, Kalimantan Barat.This study uses 69 samples of PLTD Siantan employees. The instruments used are job embeddedness scale and collectivism culture scale. The anava result shows that there is a difference in the tendency of job embeddedness in employees of generation X and generation Y in terms of collectivism culture of PLTD Siantan, Kalimantan Barat. The result shows that there is a difference of job embeddedness on generation X employees and generation Y employees. There are also cultural differences collectivism in generation X employees and generation Y employees. This means that hypothesis 1, hypothesis 2, and hypothesis 3 are accepted.Keywords:job embeddedness, collectivism culture,generation X and generation ABSTRAK: Perusahaan saat ini mengenal dua jenis generasi tenaga kerja berdasarkan rentang usia, yaitu generasi X dan generasi Y. Kedua generasi tersebut memiliki perbedaan karakteristik, salah satunya adalah job embeddedness. Tingkat job embeddedness ditemui paling tinggi pada organisasi dengan budaya kolektivisme. Budaya organisasi yang berkembang di berbagai perusahaan di Indonesia adalah budaya kolektivisme, salah satunya adalah PLTD Siantan, Kalimantan Barat. Penelitian ini bertujuan untuk (1) mengetahui perbedaan kecenderungan job embeddedness pada karyawan generasi X dan Y ditinjau dari budaya kolektivisme, (2) Mengetahui perbedaan kecenderungan job embeddedness pada karyawan generasi X dan Y, (3) Mengetahui perbedaan budaya kolektivisme pada karyawan generasi X dan Y PLTD Siantan, Kalimantan Barat. Penelitian ini menggunakan seluruh anggota populasi sebanyak 69 karyawan PLT Siantan. Instrumen yang digunakan adalah skala job embeddedness, dan budaya kolektivisme. Berdasarkan hasil anava, menunjukkan perbedaan kecenderungan job embeddedness pada karyawan generasi X dan generasi Y ditinjau dari budaya kolektivisme PLTD Siantan, Kalimantan Barat. Berdasarkan hasil analisis perbedaan rerata menunjukkan perbedaan job embeddedness pada karyawan generasi X dan karyawan generasi Y. Selain itu, terdapat juga perbedaan budaya kolektivisme pada karyawan generasi X dan karyawan generasi Y. Hal ini menjelaskan bahwa hipotesis penelitian 1, 2, dan 3 diterima.Kata kunci: job embeddedness, budaya kolektivisme, generasi X dan Y